KOMUNIKASI KEBIJAKAN PUBLIK DINAS DUKCAPIL DALAM MEMPERKENALKAN APLIKASI SIBISA DI KECAMATAN MEDAN AREA KOTA MEDAN - Aulia Alfanny; Syahrul Abidin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Public communication policies are generally motivated by the problem of lack of socialization from the Medan Area sub-district in providing direction or education on how to use the SIBISA application or website. As a result, the public has no insight and even almost blind related to the application. The lack of skills, self-awareness and public insight in using the application is what underlies the need for a deeper introduction so that the public better understands the procedures for using a technology product where the product provides population administration services and civil data registration digitally utilizing papaerless office (PLO) technology which can further unite several systematic and synergistic service systems. The method in this study uses Descriptive Qualitative research method. The results of the research conducted are the transition of attitudes and people who increase their knowledge about the SIBISA application to facilitate population management through smartphones. However, regarding the overall change in attitude, Medan Area District still needs time to use the application because the technical capabilities of both service providers and the community have not fully understood the maximum of this application as well as inadequate tools.